SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-2180
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Ethanol/Diethyl Ether Mixtures in a CI Engine

Abstract: The auto-ignition characteristics of diethyl ether (DEE)/ethanol mixtures are investigated in compression ignition (CI) engines both numerically and experimentally. While DEE has a higher derived cetane number (DCN) of 139, ethanol exhibits poor ignition characteristics with a DCN of 8. DEE was used as an ignition promoter for the operation of ethanol in a CI engine. Mixtures of DEE and ethanol (DE), i.e., DE75 (75% DEE + 25% ethanol), DE50 (50% DEE + 50% ethanol) and DE25 (25% DEE + 75% ethanol), were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The resulting minimum cell size in each direction becomes 2/2 3 = 0.125 mm. The mesh strategy is in general based on previous CFD studies in a CI engine [14].…”
Section: Spray Model Setupmentioning
confidence: 99%
“…The resulting minimum cell size in each direction becomes 2/2 3 = 0.125 mm. The mesh strategy is in general based on previous CFD studies in a CI engine [14].…”
Section: Spray Model Setupmentioning
confidence: 99%
“…where n is the level of refinement provided. The meshing strategy is further described in a previous CFD study [16].…”
Section: Cfd Models and Validationmentioning
confidence: 99%
“…Low-temperature cool flames and associated heat release during the first stage affects the heat release, the timing of the second stage ignition, and even knocking [3][4][5]. Engine studies [3][4][5][6][7] have shown that stratified combustion concepts display ignition phenomenon that is governed by both molecular transport and chemical kinetic processes.…”
Section: Introductionmentioning
confidence: 99%